2015
DOI: 10.1038/hr.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction is associated with the severity of cerebral small vessel disease

Abstract: The pathogenesis of cerebral small vessel disease, a disease that involves white matter lesions (WMLs) and cerebral microbleeds (CMBs), is thought to be associated with endothelial dysfunction. Flow-mediated dilation (FMD) has been used to measure endothelium-dependent vasodilation. The aim of this study was to investigate the association between endothelial function (as measured by FMD) and cerebral small vessel disease. Patients with a history of cerebrovascular disease and comorbidities were enrolled in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 43 publications
1
40
0
2
Order By: Relevance
“…The pathogenesis of cerebral small vessel disease, which involves white matter lesions (WMLs) and cerebral microbleeds (CMBs), is thought to be associated with endothelial dysfunction [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of cerebral small vessel disease, which involves white matter lesions (WMLs) and cerebral microbleeds (CMBs), is thought to be associated with endothelial dysfunction [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to the correlation between PAT and the ABI value, we also demonstrated a correlation between the PAT test and CVD. Nezu et al [23] reported that FMD < 4% was significantly correlated with CVD, including cerebral microbleeding. The findings from our study might support a significant correlation between PAT and CVD, as with FMD.…”
Section: Discussionmentioning
confidence: 99%
“…With the coming of the aging society and the popularization of head MRI, the detection rate of WML is getting higher and higher. The etiology of WML may be related to endothelial dysfunction, chronic cerebral hypoperfusion, blood-brain barrier destruction, and auto-regulatory dysfunction of small vessels [10,15].…”
Section: Discussionmentioning
confidence: 99%